Analisis Faktor-Faktor Yang Mempengaruhi Kecenderungan Kecurangan Akuntansi Pada Perusahaan Di Kota Batam - Erni Yanti Natalia; Suryo Budi Pranoto; Doni Asmara (LPPM Universitas Putera Batam, 2018)
Some phenomena that occurred in recent years shows the number of fraudulent practices that occur within the company that involves accounting and directors of companies in the city of Batam. In 2015, the Batam District Court again tried the alleged embezzlement case worth Rp.36 billion with the defendant Director of PT EMR Indonesia. Owner of PT EMR Indonesia sued the director and his accounting. Owner questioned the difference of financial statements of companies engaged in the trade of plastics and metal goods in Tanjung Uncang, Batam. This study aims to determine several factors that influence the tendency of accounting fraud in the existing company in Batam City. The population in this study are employees of companies working in the department of accounting, finance, purchasing and the like. Sampling technique in this research use non-probability sampling. The method used is judgmental sampling where sampling is done by based on criteria, so the total sample is 75 respondents. The result of the research shows that Compliance of Compensation has no effect on Accounting Fraud Trend with value of sig 0,829>0,05; Unethical Behavior influences Accounting Fraud Trend with sig value 0,000<0,05; Compliance of Compensation and Unethical Behavior simultaneously affect the Accounting Fraud Trend with sig value 0,000<0,05. The value of determination coefficient (R Square) of 0.267 (26.7%), which means 26.7% variation of variables can be explained by the variable Compliance and Unethical Compliance, while the remaining 73.3% is explained by variations of other variables that are not contained in this research model.